Garis-Garis Besar Pengadaan Barang Dan Jasa Pemerintah: The Outlines Of Procurement Of Goods And Services Of Government - Yusri, Yusri (Anterior Jurnal, 2017)
Procurement of Goods/Services is an activity to obtain goods/services by Ministries/Institutions/Work Unit of Regional Devices/Institutions which is its process starts from the planning of needs until completion of all activities to obtain goods/services. The procurement of government in goods and services is actually a very important part of the development process. For the government, the availability of goods and services in every government agency will be the determining factor of successful implementation of tasks and functions of each work unit. The procurement of goods and services is not only important for the government, but also important for the community because there are goods and services directly enjoyed by the general public such as roads, bridges, school buildings, hospitals, teacher services, doctors services, lawyers services etc.. The effectiveness of procurement of goods and services is achieved by providing goods and services that are truly useful as needed. To realize the effectiveness of procurement of goods and services then the determination of priority needs into the main consideration. Procurement of goods and services at work units / government agencies should be well planned so as to provide goods / services that can provide the maximum impact on the performance of government agencies in carrying out its duties and functions.